Identifikasi Segmen Pasar Mahasiswa Perguruan Tinggi Menggunakan Analisis Klaster Berdasarkan Variabel Psikografis - Hardika Khusnuliawati; Dhian Riskiana Putri (Risenologi, 2021)
The importance of the presence of higher education enables the private sector to participate in organizing academic activities in the form of higher education institutions. This causes the private higher education market to become more competitive, which implies a low number of students. Therefore, market segmentation needs to be applied to college students so that they can help to determine the model of marketing and promotional activities. The stages carried out in this study consisted of data collection, data exploration, and extracting segment. Cluster analysis was applied as a method for extracting segments of students with psychographics variables as partitioning factors. The K-Means algorithm was chosen as the method applied for cluster analysis because it produces better performance when compared to the use of K-Modes. Cluster analysis based on psychographics variables applied to this case succeeded in extracting the segment of the university students into 6 segments.